2012
DOI: 10.1016/j.cub.2012.04.016
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Interactions Underlying Tomato Flavor Preferences

Abstract: Although human perception of food flavors involves integration of multiple sensory inputs, the most salient sensations are taste and olfaction. Ortho- and retronasal olfaction are particularly crucial to flavor because they provide the qualitative diversity so important to identify safe versus dangerous foods. Historically, flavor research has prioritized aroma volatiles present at levels exceeding the orthonasally measured odor threshold, ignoring the variation in the rate at which odor intensities grow above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
300
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(311 citation statements)
references
References 19 publications
9
300
0
2
Order By: Relevance
“…Taste panels consisted of 76 persons. Panelists rated overall liking of chilled and unchilled Ailsa Craig tomatoes using a hedonic general labeled magnitude scale, as described previously (3). Chilled tomatoes were less liked than unchilled tomatoes when panelists' liking scores were compared as matched pairs using a one-tailed t test, sign test, or Wilcoxon signed rank test.…”
Section: Methodsmentioning
confidence: 99%
“…Taste panels consisted of 76 persons. Panelists rated overall liking of chilled and unchilled Ailsa Craig tomatoes using a hedonic general labeled magnitude scale, as described previously (3). Chilled tomatoes were less liked than unchilled tomatoes when panelists' liking scores were compared as matched pairs using a one-tailed t test, sign test, or Wilcoxon signed rank test.…”
Section: Methodsmentioning
confidence: 99%
“…We previously screened a large, chemically diverse population of heirloom tomato varieties, permitting us to correlate the concentrations of flavor-associated chemicals with consumer liking (16). Correlation of consumerliking scores with content of individual acetate esters as well as total acetate esters as a percentage of total volatiles indicated a significant negative correlation value (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Although this method has value, recent work has shown that the reality of taste preference is far more complex as interactions between volatiles and other flavor-associated chemicals influence perception. Consumer preference panels conducted with a large, diverse set of tomato varieties identified a set of volatiles that are positively or negatively correlated with preferences (16).…”
mentioning
confidence: 99%
“…The increase of the expression of RIN gene induces the ripening process of the fruits (Tieman et al, 2012). In the case of the EXP1 gene of the bell pepper, it had an 82.73% similarity to the Arabidopsis".…”
Section: Discussionmentioning
confidence: 99%